2019
DOI: 10.1002/jcp.28262
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor effects of curcumin: A lipid perspective

Abstract: Lipid metabolism plays an important role in cancer development due to the necessities of rapidly dividing cells to increase structural, energetic, and biosynthetic demands for cell proliferation. Basically, obesity, type 2 diabetes, and other related diseases, and cancer are associated with a common hyperactivated “lipogenic state.” Recent evidence suggests that metabolic reprogramming and overproduction of enzymes involved in the synthesis of fatty acids are the new hallmarks of cancer, which occur in an earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 129 publications
(213 reference statements)
0
27
0
Order By: Relevance
“…Due to the presence of conjugated double bonds in its chemical structure, this polyphenol serves as an effective electron donor to counteract the production of reactive oxygen species (ROS) in many redox reactions [ 3 ], acting as a potent antioxidant. In addition, it has other important biological functions, such as anti-inflammatory, antitumor, antimicrobial, and antiviral ones [ 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the presence of conjugated double bonds in its chemical structure, this polyphenol serves as an effective electron donor to counteract the production of reactive oxygen species (ROS) in many redox reactions [ 3 ], acting as a potent antioxidant. In addition, it has other important biological functions, such as anti-inflammatory, antitumor, antimicrobial, and antiviral ones [ 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The most widely previously studied of these three compounds is the natural polyphenol curcumin; turmeric, the spice most associated with Indian cuisine is comprised of approximately 95% of curcumin and curcuminoid derivatives (Vishwakarma et al, 2018). Although curcumin has been intensively studied as cancer therapy for many years, the chemical has several major disadvantages as a potential drug including its very low solubility in water and its rapid first‐pass metabolism by the liver via glucuronidation or sulphation (Lagoa, Silva, Rodrigues, & Bishayee, 2019; Naeini et al, 2019). Curcumin combined in micelles with plant lecithin, in contrast, has almost 100‐fold greater bioavailability in terms of both C max and AUC, with safe peak plasma C max concentrations in the low micromolar levels (Belcaro, Hosoi, Pellegrini, Appendino, & Ippoito, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Rather, biological process enrichment analysis, showed that alterations were predominantly seen in metabolic processes, particularly in lipid and protein metabolism. Metabolic reprogramming is a well-established hallmark of cancer and upregulation of lipid metabolism is strongly associated with tumorigenesis, particularly in BrCa (43)(44)(45). The significant upregulation of lipoprotein lipase (LPL) expression in our model suggests increased utilisation of circulating fatty acids.…”
Section: Discussionmentioning
confidence: 84%